Leopard population density varies across habitats and management strategies ina mixed-use Tanzanian landscape - Searle, C; Smit, J; Strampelli, P; Mkuburo, L; Ikanda, D; Macdonald, D; Loveridge, A; Dickman, A (Elsevier, 2021)
With large carnivores undergoing widespread range contractions across Africa, effective monitoring across mixed-use landscapes should be considered a priority to identify at-risk populations and prioritise conservation actions. We provide the first comparison of leopard population density within different components of a mixed-use landscape in Tanzania, via spatially explicit capture-recapture (SECR) modelling of camera trap data from the Ruaha-Rungwa landscape in 2018 and 2019. Population density was highest in highly-productive Acacia-Commiphora habitat in the core tourist area of Ruaha National Park (6.81 ± 1.24 leopards per 100 km2). The next highest density (4.23 ± 1.02 per 100 km2) was estimated in similar habitat in a neighbouring community-managed area (Idodi-Pawaga MBOMIPA WMA). Lowest densities were estimated in miombo (Brachystegia-Jubelnardia) woodland habitat, both in a trophy hunting area (Rungwa Game Reserve; 3.36 ± 1.09 per 100 km2) and inside the National Park (3.23 ± 1.25 per 100 km2). Population density was highly correlated with prey abundance, suggesting that variation in leopard density may be primarily driven by availability of prey, which likely varies with habitat types and anthropogenic impacts. Anthropogenic mortality may also have a direct influence on leopard in more impacted areas, but further research is required to investigate this. Our findings show that a hunting area with significant protection investment supports a leopard density comparable to similar habitat in a photographic tourism area. We also provide evidence that community-managed areas have the potential to effectively conserve large carnivore populations at relatively high densities, but may be vulnerable to edge effects.